LEADERSHIP STYLES IN SMES: AN EXPLORATORY STUDY IN ROMANIA - Radu OGARCĂ; Liviu CRĂCIUN; Laurențiu MIHAI (Management & Marketing)
The manager’s leadership styles define the way a manager acts behaves and takes decisions in certain situations and has a direct influence upon the employees’ well-being. In a small and medium enterprise setting, unlike in a large enterprise, the employees are feeling the influence of the leadership style in a much more direct and personal way, due to the small number of hierarchical levels and the constant interaction between the owner/manager and the employees. The present paper focuses on analyzing how the employees of SMEs from Oltenia and Muntenia Regions of Romania perceive their superiors’ leadership styles. In order to meet this goal, we have used a 21 question survey, based on which we could determine the leadership style (Autocratic, Democratic or Laissez-faire) of the superior, as it is perceived by each respondent. The survey has been applied on a sample of cca. 300 employees from small and medium enterprises from Oltenia, and approximately 130 responses have been used in the actual research. The results of this study will be used in a further research, in which we aim to compare the way the managers perceive their own leadership style and how it is perceived by their employees.